2023
DOI: 10.1088/2057-1976/acd784
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of a single-level customized cage screw fixation for anterior cervical discectomy and fusion in the cervical spine: an in-silico study

Abstract: The usual surgical choice of customized cage fixation is anterior cervical discectomy and fusion (ACDF) for cervical spondylosis with disc herniation. The safe and successful cage fixation for ACDF surgery benefits patients with cervical disc degenerative disease by easing their discomfort and regaining function. The cage prevents mobility between the vertebrae by using cage fixation to anchor the neighbouring vertebrae. The goal of the current study is to develop a customized cage-screw implant for single-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…The results indicated that the stress on Ti screws ranged from 84 MPa to 121 MPa, which is significantly below their yield stress. The study employed an internal fixation method, and the stress results were not compared with relevant approaches for entry route fixation [47]. Duan Y's team compared the postoperative stress levels of three internal fixation techniques.…”
Section: Analysis Of the Impact Of Posterior Screw Insertion Methods ...mentioning
confidence: 99%
“…The results indicated that the stress on Ti screws ranged from 84 MPa to 121 MPa, which is significantly below their yield stress. The study employed an internal fixation method, and the stress results were not compared with relevant approaches for entry route fixation [47]. Duan Y's team compared the postoperative stress levels of three internal fixation techniques.…”
Section: Analysis Of the Impact Of Posterior Screw Insertion Methods ...mentioning
confidence: 99%
“…15 The intricate geometry of the vertebra necessitated the use of a tetrahedral element for volume meshing, with mesh sensitivity analysis refined to less than 3% error. 2930…”
Section: Methodsmentioning
confidence: 99%